2006
DOI: 10.21273/jashs.131.2.284
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Linolenic Acid in Lefad7 Mutant Tomato Changes the Volatile Profile and Sensory Perception of Disrupted Leaf and Fruit Tissue

Abstract: Six-carbon aldehydes and alcohols formed by tomato (Lycopersicon esculentum Mill.) leaf and fruit tissue following disruption are believed to be derived from the degradation of lipids and free fatty acids. Collectively, these C-6 volatiles comprise some of the most important aroma impact compounds. If fatty acids are the primary source of tomato volatiles, then an alteration in the fatty acid composition such as that caused by a mutation in the chloroplastic omega-3-fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Similar patterns of reductions in LA, LeA, and OA during storage could explain the decrease in the total levels of aldehydes. However, the decline in C 6 aldehydes from the ETH-treated 'Tianbao' fruit was not likely to have been caused by changes in FA precursors during fruit ripening, although previous studies have shown that modification of FA profiles can cause changes in the levels of volatile compounds (Canoles and Beaudry, 2006). Such a result may be due to the higher activities of ADH or AAT in fruit treated with ETH, which can catalyze the conversion of more aldehydes to downstream products, although increased levels of LOX and HPL activity have been simultaneously observed in ETH-treated fruit.…”
Section: Discussionmentioning
confidence: 77%
“…Similar patterns of reductions in LA, LeA, and OA during storage could explain the decrease in the total levels of aldehydes. However, the decline in C 6 aldehydes from the ETH-treated 'Tianbao' fruit was not likely to have been caused by changes in FA precursors during fruit ripening, although previous studies have shown that modification of FA profiles can cause changes in the levels of volatile compounds (Canoles and Beaudry, 2006). Such a result may be due to the higher activities of ADH or AAT in fruit treated with ETH, which can catalyze the conversion of more aldehydes to downstream products, although increased levels of LOX and HPL activity have been simultaneously observed in ETH-treated fruit.…”
Section: Discussionmentioning
confidence: 77%
“…Similar findings were found when the expression of a yeast Δ‐9 desaturase gene was altered to produce higher concentrations of oleic acid and linoleic acid, which caused hexanal and 1‐hexanol to be more than two times greater than the control (Wang and others 1996). Breeding tomatoes with higher levels of linoleic acid and lower levels of linolenic acid caused an increase in hexanal and a decrease in ( Z )‐3‐hexenal formation (Canoles and others 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Hexanal and 1‐hexanol were more than two times greater in the tomato with higher levels of fatty acids than the control (Wang and others 1996). Tomatoes with higher levels of linoleic acid and lower levels of linolenic acid caused an increase in hexanal and a decrease in ( Z )‐3‐hexenal (Canoles and others 2006). Certain fatty acids have been found to correlate with the formation of some of their successor flavor volatiles.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is not unlikely that the unsaturated aldehyde fraction and, particularly, hexanal, may be due to lipid peroxidation during sampling and freezing (Ma et al, 2007). It has also been reported that hexanal increases with increasing harvest maturity, which could lead to development of off-flavours in stored melon and fresh-cut products (Beaulieu & Grimm, 2001) and in tomato (Canoles et al, 2006). However, hexanal slightly changes during PS senescence compared with other NILs (Obando-Ulloa et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…ever, shows many aroma compounds, most of them aldehydes (Table 1). Even though some aldehydes are not easily detectable by the human nose, others have a low human detection threshold (Baldwin, 2002;Beaulieu & Baldwin, 2002;Canoles, Beaudry, Li, & Howe, 2006), and are important for the flavour of tomato, cucumber, peppers and other vegetables (Baldwin, 2002;Canoles et al, 2006). Aldehydes with low molecular weight are associated with immature stages in climacteric Cantaloupe melons (Beaulieu & Grimm, 2001).…”
Section: Discussionmentioning
confidence: 99%